2001
DOI: 10.1093/ei/39.4.627
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cocaine Prices on Crime

Abstract: The relationship between cocaine prices and crime has critical implications for U.S. drug policy, but is theoretically indeterminate because cocaine price changes affect crime through changes in both cocaine consumption and expenditures. This paper investigates this relationship in annual data from 1981–95 on 29 large U.S. cities, accounting for simultaneity by using two‐stage least squares with measures of wholesale supply factors and retail enforcement intensity as instruments for cocaine prices. Controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
3
22
1
Order By: Relevance
“…As illustrated in Table 1, most used U.S. state-level data on beer taxes, examining associations with rape and sexual assault crime data (Cook & Moore, 1993; Desimone, 2001; Zimmerman & Benson, 2007) or self-reported rape and sexual assault victimization data (Markowitz, 2005). The majority of studies concluded that higher alcohol prices and taxes were associated with lower rates of sexual violence at the state level (Cook & Moore, 1993; Desimone, 2001; Grossman & Markowitz, 1999; Zimmerman & Benson, 2007). Markowitz (2005) did not find a statistically significant relationship between sexual violence and higher taxes but did report lower rates of general physical assaults overall.…”
Section: Evidence Linking Alcohol Policy and Sexual Violencementioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Table 1, most used U.S. state-level data on beer taxes, examining associations with rape and sexual assault crime data (Cook & Moore, 1993; Desimone, 2001; Zimmerman & Benson, 2007) or self-reported rape and sexual assault victimization data (Markowitz, 2005). The majority of studies concluded that higher alcohol prices and taxes were associated with lower rates of sexual violence at the state level (Cook & Moore, 1993; Desimone, 2001; Grossman & Markowitz, 1999; Zimmerman & Benson, 2007). Markowitz (2005) did not find a statistically significant relationship between sexual violence and higher taxes but did report lower rates of general physical assaults overall.…”
Section: Evidence Linking Alcohol Policy and Sexual Violencementioning
confidence: 99%
“…SV: Beneficial effects on rates of SV based on self-report and law enforcement data in four studies (Cook & Moore, 1993; Desimone, 2001; Grossman & Markowitz, 1999; Zimmerman & Benson, 2007); null effects on self-reported rates of SV in two studies (Herttua, Mäkelä, Martikainen, & Sirén, 2008; Markowitz, 2005)…”
Section: Tablementioning
confidence: 99%
“…Chaloupka and Saffer find similar results; higher beer taxes lower the rates of rape, robbery, and homicide, but not physical assault. Desimone (2001) conducts a similar analysis and finds a negative relationship between the state beer tax and assaults, rapes, and some types of property crimes. However, all of these studies only analyze crimes that have been reported to the police and are therefore limited in their generalizability.…”
Section: Introductionmentioning
confidence: 91%
“…Also, in a similar context, for example, to the U.S. case of Bandyopadhyay and McCannon (2014), we also explore new deterrence variables that reflect the arbitrary discretion in the use of this important instrument to prosecutors, i.e., summary prosecution. 4 The question of cross-crime spillover effects, through arrest or imprisonment, has been addressed in Holtman and Yap (1978), Hakim et al (1984), Cameron (1987), Benson et al (1998), Resignato (2000), Desimone (2001), or Kuziemko and Levitt (2004), although, as shown in Sect. 2, their analytic frameworks are not the same (or as much integrated) as the one used in this paper.…”
Section: Introductionmentioning
confidence: 99%